Concepts and Applications of Therapeutic Interchange in Bioequivalence and Generic Drugs - Troja , Eva; Deda , Leonard (Novel Aspects on Pharmaceutical Research Vol. 8, 2023)
In this chapter, an outline detailing the concepts and applications of Therapeutic Interchange in Bioequivalence and Generic Drugs and to review scientific criteria for marketing authorization of generic products is presented. Bioequivalence studies are very important for the drug development phase for both new drugs and generic equivalents in the pharmaceutical industry. Their description and the results of generic products are a significant part of the registration dossier submitted by regulatory authorities. The importance of bioequivalence studies is increasing also due to the large growth of the production and consumption of generic products. Bioequivalence studies play a key role in establishing interchangeability (therapeutic equivalence) and substitution of generic drugs, allowing pharmacists to substitute them without requiring prescriber approval. These studies contribute to cost-effectiveness, improve public health outcomes and boost access to essential drugs.